Mechanical and functional properties of nano-structured polyvinylidene fluoride and its carbon nanotube composites - Chen, Xuelong (2016)
Polyvinylidene Fluoride (PVDF) is one type of semicrystalline fluoropolymers that has been widely used in automotive and chemical industries, semiconductor, biomedical and sensor applications; owing to its superior chemical resistance, excellent mechanical properties and unique electronic properties. Polymeric composites containing nanoscale fillers, such as graphene, carbon nanotube (CNTs) or nanoclay often render polymers with interesting mechanical, structural, electrical, optical and many other functional properties. The objective of this work is to improve mechanical and functional properties of PVDF by the advantageous introduction of CNTs. Studies will focus on the preparation methodology of PVDF/CNTs composites with uniform morphology, the interaction between CNTs and polymer matrix and surface treatment of CNTs.